Enrollment and clients' satisfaction with a community-based health insurance scheme: a community-based survey in Northwest Ethiopia - Ashenafi Kibret Sendekie; Ayenew Hailu Gebremichael; Melkamu Workie Tadesse (BMC, 2024)
Abstract Background Although the Ethiopian government has implemented a community-based health insurance (CBHI) program, community enrollment and clients' satisfaction have not been well investigated in Gondar Zuria district, Northwest Ethiopia. This study assessed CBHI scheme enrollment, clients' satisfaction, and associated factors among households in the district. Methods A community-based cross-sectional survey assessed CBHI scheme enrollment and clients' satisfaction among households in Gondar Zuria district, Northwest Ethiopia, from May to June 2022. A systematic random sampling method was used to select the study participants from eligible households. A home-to-home interview using a structured questionnaire was conducted. Data were analysed using the statistical packages for social sciences version 26. Logistic regression was used to identify variables associated with enrollment and clients' satisfaction. A p-value < 0.05 was considered statistically significant. Results Out of 410 participants, around two-thirds (64.9%) of the participants were enrolled in the CBHI scheme. Residency status (AOR = 1.38, 95% CI: 1.02-5.32; p = 0.038), time taken to reach a health facility (AOR = 1.01, 95% CI: 1.00-1.02; p = 0.001), and household size (AOR = 0.77, 95% CI: 0.67-0.88; p < 0.001) were significantly associated with CBHI scheme enrollment. Two-thirds (66.5%) of enrolled households were dissatisfied with the overall services provided; in particular, higher proportions were dissatisfied with the availability of medication and laboratory tests (88.7%). Household size (AOR = 1.31, 95% CI: 1.01-2.24; p = 0.043) and waiting time to get healthcare services (AOR = 3.14, 95% CI: 1.01-9.97; p = 0.047) were predictors of clients' satisfaction with the CBHI scheme services. Conclusion Although a promisingly high proportion of households were enrolled in the CBHI scheme, most of them were dissatisfied with the service. Improving waiting times to get health services, improving the availability of medications and laboratory tests, and other factors should be encouraged.